2010
DOI: 10.1017/s0959270910000195
|View full text |Cite
|
Sign up to set email alerts
|

Avian population survey in the Floreana highlands: is Darwin’s Medium Tree Finch declining in remnant patches ofScalesiaforest?

Abstract: SummaryIsland species typically exist in pathogen and predator sparse environments before human settlement, and are particularly vulnerable to the impacts of invasive species. In this study, we used the variable circular-plot method to estimate the density of birds in the highlands of Floreana Island, Galápagos Archipelago, where introduced parasites, predators, and habitat degradation are a known threat to endemic species. We recorded the number of birds seen and heard at 15 locations near Cerro Pajas Volcano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 29 publications
3
38
2
Order By: Relevance
“…Our population estimate of between 3900 and 4700 territories of Medium Tree‐Finches in 2015 and 2016 (Table ) was higher than previous estimates based on studies conducted in 2008 (1620, O'Connor et al. , 2292, Peters and Kleindorfer ) and 2013 (2537 males, Peters and Kleindorfer ). Our density estimates (1.8–2.9 territories/ha) were more than double those calculated in either 2008 (0.6–1.0 birds/ha) (O'Connor et al.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our population estimate of between 3900 and 4700 territories of Medium Tree‐Finches in 2015 and 2016 (Table ) was higher than previous estimates based on studies conducted in 2008 (1620, O'Connor et al. , 2292, Peters and Kleindorfer ) and 2013 (2537 males, Peters and Kleindorfer ). Our density estimates (1.8–2.9 territories/ha) were more than double those calculated in either 2008 (0.6–1.0 birds/ha) (O'Connor et al.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, O'Connor et al. () described a decline in the population of the endemic Medium Tree‐Finches ( Camarhynchus pauper ) on Floreana between 2004 and 2008. Given these reports of disappearing and declining populations of landbirds on Floreana, our objective was to conduct a comprehensive survey of landbirds encompassing the entire island.…”
mentioning
confidence: 99%
“…Some authors have proposed birds should avoid selecting nesting sites where they are more exposed to parasites, and that selection for good sites would be the first line of defense against parasitism (Loye andCarroll 1991, 1998;O'Connor et al 2010b). We did not observe behavior by Red-crested Cardinals that suggested increased use of isolated patches of forest and earlier onset of breeding to avoid the higher parasite prevalence typical of riverine forest patches.…”
Section: Discussionmentioning
confidence: 99%
“…Different fieldwork activities were done during the months January to March, which coincides with the onset of peak breeding activity in Darwin's finches. Birds were mist-netted and observed in the Scalesia forest at the base of Cerro Pajas volcano (1°17′S, 90°27′W, elevation 250-350 m) (O'Connor et al, 2010a All guidebooks refer to three Darwin's tree finch species on Floreana Island: small tree finch, medium tree finch, and large tree finch (C. parvulus, C. pauper and C. psittacula, respectively). But a recent study by Kleindorfer et al (2014a) found only two genetic groups and one hybrid cluster of tree finches on Floreana Island.…”
Section: Study Locationmentioning
confidence: 99%